Artificial graphite negative electrode material and preparation and application thereof
Through the coating and high-temperature treatment of modifiers and asphalt and resin, the problem of poor structural stability of artificial graphite negative electrode materials is solved, the energy density and cycling performance of the battery are improved, and the service life of the lithium battery is extended.
Patent Information
- Application Number
- CN202411265253.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, artificial graphite negative electrode materials have many surface defects and poor structural stability, resulting in low energy density.
Modifiers are used to work together with asphalt and resin to form a tight cladding layer through the calcination, carbonization and graphitization steps, which improves the density and structural stability of the graphite surface and enhances the energy density and cyclic stability of the negative electrode material.
It improves the energy density of the battery and the deformation durability of the negative electrode material, increases the capacity and service life of the lithium battery, and improves the charging speed and cycling performance.
Smart Images

Figure BDA0005036942130000081
Abstract
Description
Technical Field
[0001] The invention relates to a graphite negative electrode material for a lithium battery, and in particular to an artificial graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] As a secondary battery system, lithium-ion batteries use two different lithium-ion compounds that can reversibly embed and extract lithium ions, respectively, as the positive and negative electrodes of the battery. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + The electrolyte is then embedded in the negative electrode after being removed from the positive electrode, and the negative electrode is in a lithium-rich state; the opposite is true during discharge. Lithium-ion batteries have a wide range of market demands due to their high safety and high energy density, especially in the application of electric vehicles, where they have a huge market value.
[0003] According to the different properties of raw materials, the mainstream graphite negative electrode materials for lithium batteries are natural graphite, artificial graphite and silicon-carbon composite negative electrode. Artificial graphite has good electrical conductivity, thermal conductivity and chemical stability, high specific surface area and good chemical reactivity. In the application of battery negative electrode materials, artificial graphite can provide higher lithium storage capacity and better cycle stability, so it has been widely used.
[0004] However, in the prior art, artificial graphite negative electrode materials have many surface defects and poor structural stability, which leads to low energy density of the negative electrode materials and affects the performance of the artificial graphite negative electrode materials. Summary of the invention
[0005] The purpose of the present invention is to provide an artificial graphite negative electrode material and its preparation and application, which solves the problem that the artificial graphite negative electrode material in the prior art has many surface defects and poor structural stability, thereby leading to low energy density of the negative electrode material. A modifier is used to work together with asphalt and resin to improve the compactness of the coating layer. The carbonization and graphitization steps improve the density and structural stability of the graphite surface, which is helpful to improve the energy density of the battery, make the deformation durability of the negative electrode material higher, and the prepared battery has good first discharge efficiency.
[0006] In order to achieve the above object, the present invention provides a method for preparing an artificial graphite negative electrode material, the method comprising:
[0007] (1) Crushing step: crushing the artificial graphite raw material once to obtain crushed artificial graphite raw material;
[0008] (2) calcining step: calcining the crushed artificial graphite raw material at 160° C. to obtain a calcined artificial graphite raw material;
[0009] (3) a crushing and shaping step: the calcined artificial graphite raw material is subjected to secondary crushing and then spheroidization to obtain a spheroidized artificial graphite raw material;
[0010] (4) granulation step: mixing and granulating the spheroidized artificial graphite raw material and the coating material to obtain an artificial graphite precursor;
[0011] Wherein, the coating material is a mixture of asphalt, resin and modifier;
[0012] The modifier is a mixture of sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate;
[0013] (5) Carbonization step: carbonizing the artificial graphite precursor at 700° C. to 1100° C. to obtain carbonized graphite particles;
[0014] (6) Graphitization step: treating the carbonized graphite particles at a temperature of 2600° C. to 3200° C. to obtain a primary product of artificial graphite negative electrode material.
[0015] The one-time crushing of step (1) of the method makes the particle size of the crushed artificial graphite raw material uniform, which helps to improve the subsequent battery rate and cycle performance. The calcination of step (2) removes the volatile matter therein, improves the purity and crystallinity, and has a promoting effect on improving the mechanical strength, conductivity and oxidation resistance of the negative electrode material. Among them, the volatile matter removed by calcination includes water, hydrogen and methane. The crushing and shaping of step (3) reduces the edges and corners of the artificial graphite raw material, improves the sphericity, and is conducive to the full contact and mixing of the raw material and subsequent auxiliary materials. The asphalt in step (4) is coated on the surface of the spheroidized artificial graphite raw material to form a "protective cover" of the shell structure. When used, it can not only avoid the co-embedding and mixing of lithium ions and solvents and inhibit the decomposition of the electrolyte, but also improve the compatibility of the negative electrode material and the electrolyte, effectively improve the first charge reversible capacity, cycle stability and battery rate performance of the negative electrode material, and help the negative electrode material to be finalized, so that the capacity of the lithium battery is larger, the service life is longer, and the charging speed is faster. At the same time, the resin is coated on the surface of the negative electrode, so that the formed coating layer is tighter and firmer. The modifier is used to modify the surface of the spheroidized artificial graphite raw material, and the modifier is grafted on the surface of the spheroidized artificial graphite raw material to work together with asphalt and resin to improve the tightness of the coating layer. The carbonization in step (5) can further remove the volatile components in the artificial graphite precursor, shrink the volume of the artificial graphite precursor, and improve its thermal stability. The graphitization in step (6) is to transform the carbon atoms from a disorderly and irregular arrangement to a regularly arranged hexagonal planar network structure at high temperature, that is, from a chaotic layer structure to an ordered graphite crystal structure, the purpose of which is to obtain the properties of graphite such as high electrical conductivity, high thermal conductivity, corrosion resistance, and friction resistance.
[0016] Preferably, the mass ratio of the coating material to the spheroidized artificial graphite raw material is 10:(30-80); if the amount of coating material added is too little, a complete "protective cover" cannot be formed, which is not conducive to improving the discharge capacity and structural stability of the negative electrode material. If the amount of coating material added is too much, the binding force between the particles will be weakened, making the coating layer easy to fall off from the graphite surface, thereby reducing the charge and discharge efficiency and increasing the cost.
[0017] The mass ratio of the asphalt, the resin and the modifier is 1:(2.5-3.5):(0.2-0.8).
[0018] Preferably, the mass ratio of sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate is 1:(0.5-0.8):(0.2-0.5). Through the grafting of sodium dodecylbenzene sulfonate, the artificial graphite precursor has good wettability and dispersibility, and tetrabutylammonium sulfate can be grafted between the artificial graphite precursor and sodium dodecylbenzene sulfonate. At the same time, melamine polyphosphate reacts with the active groups on the surface of the artificial graphite precursor, and synergizes with tetrabutylammonium sulfate to increase the interlayer spacing of the graphitized negative electrode material, which is beneficial to improve the transmission of lithium ions. At the same time, it works together with asphalt and resin to improve the compactness of the coating layer. After carbonization and graphitization steps, an artificial graphite negative electrode material is obtained, which makes the structure of the negative electrode material more stable and the specific surface area larger. When used in batteries in the future, it can improve the lithium insertion characteristics, so that the battery has a good long cycle life and high rate performance.
[0019] Preferably, the artificial graphite raw material is a mixture of petroleum coke and needle coke in a mass ratio of 1:(5-8). The mixture of petroleum coke and needle coke is used as the artificial graphite raw material. Both contain high-purity carbon and have good strength, high electrical conductivity and high thermal conductivity.
[0020] Preferably, or the granulation step is: mixing the modifier and water in a weight ratio of 1: (3-10) to obtain a modified dispersion; stirring the spheroidized artificial graphite raw material and the modified dispersion at a temperature of 50-60° C. to obtain an artificial graphite modified primary product; mixing and granulating the artificial graphite modified primary product with a mixture of asphalt and resin to obtain the artificial graphite precursor;
[0021] The mass ratio of the spheroidized artificial graphite raw material to the modified dispersion is 10:(0.09-2), and the mass ratio of the artificial graphite modified primary product to the asphalt and the resin is (10-12):1:(2-4). The artificial graphite modified primary product is mixed and coated with a mixture of asphalt and resin, so that the asphalt and the resin are coated on the surface of the modified artificial graphite precursor, which can further improve the structural stability of the artificial graphite negative electrode material and facilitate the transmission of lithium ions.
[0022] Preferably, the particle size of the crushed artificial graphite raw material is 3 to 10 μm, and the particle size of the spheroidized artificial graphite raw material is 5 to 20 μm. When artificial graphite negative electrode is used in a battery, during the charge and discharge process, larger particles are prone to structural expansion and short cycle life, while small particles affect the battery energy density. Therefore, it is necessary to control the particle size of the artificial graphite raw material, which is beneficial to improving the structural stability of the negative electrode material and the cycle performance of the battery.
[0023] Preferably, the volatile matter of the artificial graphite raw material after calcination is ≤1%; the calcination time at 160°C is 5 to 7 hours; the carbonization time is 2 to 5 hours, and the treatment time at 2600°C to 3200°C is 20 to 35 hours. The volatile matter in the artificial graphite raw material is removed by calcination. If the volatile matter is not discharged in time, a large amount of volatile matter will accumulate in the subsequent carbonization and graphitization process, which will cause certain safety hazards and affect the quality of the graphitized negative electrode material. The carbonization step further removes the volatile matter in the artificial graphite raw material, and at the same time makes the graphitized negative electrode material have better high temperature and high conductivity, which is beneficial to improve the structural stability and quality of the graphitized negative electrode material.
[0024] More preferably, the asphalt is petroleum asphalt or coal asphalt, and the resin is phenolic resin or epoxy resin.
[0025] Preferably, the method further comprises: screening and demagnetizing the primary artificial graphite negative electrode material to obtain the artificial graphite negative electrode material. During the graphitization process, particles may stick together or become smaller. Such uneven particle distribution is not conducive to the stability of the negative electrode material. Therefore, the primary graphitized particles with too large or too small particle sizes are screened out by screening. The particles are then demagnetized by a demagnetizer to improve the quality and stability of the artificial graphite negative electrode material. The magnetic substance content of the artificial graphite negative electrode material after demagnetization is ≤0.2ppm
[0026] More preferably, the particle size of the artificial graphite negative electrode material is 10 to 22 μm.
[0027] The invention provides an artificial graphite negative electrode material prepared by the preparation method.
[0028] Preferably, the particle size of the artificial graphite negative electrode material is 10 to 22 μm.
[0029] The present invention provides an application of the artificial graphite negative electrode material in the battery field.
[0030] The artificial graphite negative electrode material of the present invention and its preparation and application solve the problem that the artificial graphite negative electrode material in the prior art has many surface defects and poor structural stability, thereby resulting in low energy density of the negative electrode material, and has the following advantages:
[0031] 1. In the granulation step of the present invention, the surface of the spheroidized artificial graphite raw material is coated with asphalt to form a "protective cover" with an outer shell structure. When used, it can not only avoid the co-embedding and mixing of lithium ions and solvents and inhibit the decomposition of the electrolyte, but also improve the compatibility of the negative electrode material and the electrolyte. At the same time, the resin is coated on the surface of the negative electrode to make the formed coating layer tighter and firmer.
[0032] 2. The present invention uses modifiers (sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate) to work together with asphalt and resin to improve the compactness of the coating layer, and then through carbonization and graphitization steps, the structure of the prepared negative electrode material is more stable, the density of the graphite surface is improved, which helps to improve the energy density of the battery and make the deformation durability of the negative electrode material higher. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The sources of the raw materials involved in the following examples are as follows:
[0035] Asphalt was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0036] Phenolic resin and epoxy resin were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0037] Sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0038] Example 1
[0039] A method for preparing an artificial graphite negative electrode material, the method comprising:
[0040] (1) Crushing step: crushing the artificial graphite raw material once to obtain crushed artificial graphite raw material; the artificial graphite raw material is a mixture of petroleum coke and needle coke, the weight ratio of petroleum coke to needle coke is 1:5, and the particle size of the crushed artificial graphite raw material is 3 μm.
[0041] (2) Calcination step: calcining the crushed artificial graphite raw material at 160° C. for 5 h to obtain a calcined artificial graphite raw material, wherein the volatile matter of the calcined artificial graphite raw material is ≤1%.
[0042] (3) Crushing and shaping step: The calcined artificial graphite raw material is crushed for a second time and then spheroidized to obtain spheroidized artificial graphite raw material with a particle size of 5 μm.
[0043] (4) Granulation step: mixing and granulating the spheroidized artificial graphite raw material and the coating material to obtain an artificial graphite precursor; wherein the weight ratio of the coating material to the spheroidized artificial graphite raw material is 10:30, the coating material is petroleum asphalt, phenolic resin and modifier in a weight ratio of 1:2.5:0.2; the modifier is sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate in a weight ratio of 1:0.5:0.2.
[0044] (5) Carbonization step: The artificial graphite precursor is carbonized at 700°C for 2 h to obtain carbonized graphite particles.
[0045] (6) Graphitization step: The carbonized graphite particles are treated at a temperature of 2600° C. for 20 h to obtain a preliminary product of artificial graphite negative electrode material.
[0046] (7) Screening and demagnetization step: After screening and demagnetizing the primary artificial graphite negative electrode material, an artificial graphite negative electrode material with a magnetic substance content of ≤0.2ppm and a particle size of 10μm is obtained.
[0047] Example 2
[0048] A method for preparing an artificial graphite negative electrode material is basically the same as that in Example 1, except that:
[0049] In step (1), the weight ratio of petroleum coke to needle coke is 1:6.5, and the particle size of the crushed artificial graphite raw material is 7 μm;
[0050] In step (2), the calcination temperature is 180°C and the time is 6 hours;
[0051] In step (3), the particle size of the spheroidized artificial graphite raw material is 12 μm;
[0052] In step (4), the weight ratio of the coating material to the spheroidized artificial graphite raw material is 10:50, the coating material is a mixture of petroleum asphalt, phenolic resin and modifier in a weight ratio of 1:3:0.5, and the modifier is sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate in a weight ratio of 1:0.7:0.4;
[0053] In step (5), the carbonization temperature is 900°C and the time is 3h;
[0054] In step (6), the graphitization temperature is 3000°C and the time is 25h;
[0055] In step (7), the particle size of the artificial graphite negative electrode material is 16 μm.
[0056] Example 3
[0057] A method for preparing an artificial graphite negative electrode material is basically the same as that in Example 1, except that:
[0058] In step (1), the weight ratio of petroleum coke to needle coke is 1:8, and the particle size of the crushed artificial graphite raw material is 10 μm;
[0059] In step (2), the calcination temperature is 200°C and the time is 7h;
[0060] In step (3), the particle size of the spheroidized artificial graphite raw material is 20 μm;
[0061] In step (4), the weight ratio of the coating material to the spheroidized artificial graphite raw material is 10:80, the coating material is a mixture of petroleum asphalt, phenolic resin and modifier in a weight ratio of 1:3.5:0.8, and the modifier is sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate in a weight ratio of 1:0.8:0.5;
[0062] In step (5), the carbonization temperature is 1100°C and the time is 5 hours;
[0063] In step (6), the graphitization temperature is 3200°C and the time is 35h;
[0064] In step (7), the particle size of the artificial graphite negative electrode material is 22 μm.
[0065] Example 4
[0066] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0067] In step (4), the modifier and water are mixed in a weight ratio of 1:3 to obtain a modified dispersion; the spheroidized artificial graphite raw material and the modified dispersion are stirred at a temperature of 50°C for 0.5h to obtain a modified artificial graphite primary product, and the modified artificial graphite primary product is mixed and granulated with a mixture of petroleum asphalt and phenolic resin to obtain an artificial graphite precursor. The mass ratio of the spheroidized artificial graphite raw material to the modified dispersion is 10:0.09, and the mass ratio of the modified artificial graphite primary product to the petroleum asphalt and phenolic resin is 10:1:2.
[0068] Example 5
[0069] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0070] In step (4), the modifier and water are mixed in a weight ratio of 1:7 to obtain a modified dispersion. The spheroidized artificial graphite raw material and the modified dispersion are stirred at a temperature of 55°C for 45 minutes to obtain a modified artificial graphite primary product, and the modified artificial graphite primary product is mixed and granulated with a mixture of petroleum asphalt and phenolic resin to obtain an artificial graphite precursor. The mass ratio of the spheroidized artificial graphite raw material to the modified dispersion is 10:1.5, and the mass ratio of the modified artificial graphite primary product to the petroleum asphalt and phenolic resin is 10:1:3.
[0071] Example 6
[0072] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0073] In step (4), the modifier and water are mixed in a weight ratio of 1:10 to obtain a modified dispersion. The spheroidized artificial graphite raw material and the modified dispersion are stirred at a temperature of 60°C for 1 hour to obtain a modified artificial graphite primary product, and the modified artificial graphite primary product is mixed and granulated with a mixture of petroleum asphalt and phenolic resin to obtain an artificial graphite precursor. The mass ratio of the spheroidized artificial graphite raw material to the modified dispersion is 10:2, and the mass ratio of the modified artificial graphite primary product to the petroleum asphalt and phenolic resin is 10:1:4.
[0074] Comparative Example 1
[0075] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0076] In step (4), the weight ratio of the coating material to the spheroidized artificial graphite raw material is 10:29.
[0077] Comparative Example 2
[0078] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0079] In step (4), the weight ratio of the coating material to the spheroidized artificial graphite raw material is 10:81.
[0080] Comparative Example 3
[0081] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0082] In step (4), the weight ratio of the coating material to the spheroidized artificial graphite raw material is 10:50, the coating material comprises a mixture of petroleum asphalt, phenolic resin and a modifier in a weight ratio of 1:3:0.5, and the modifier comprises sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate in a weight ratio of 1:0.4:0.1.
[0083] Comparative Example 4
[0084] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0085] In step (4), the weight ratio of the coating material to the spheroidized artificial graphite raw material is 10:50, the coating material comprises a mixture of petroleum asphalt, phenolic resin and a modifier in a weight ratio of 1:3:0.5, and the modifier comprises sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate in a weight ratio of 1:0.9:0.6.
[0086] Comparative Example 5
[0087] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0088] In step (4), the modifier comprises sodium dodecylbenzene sulfonate and melamine polyphosphate in a weight ratio of 1:0.4.
[0089] Comparative Example 6
[0090] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0091] In step (4), the modifier comprises sodium dodecylbenzene sulfonate and tetrabutylammonium sulfate in a weight ratio of 1:0.7.
[0092] Comparative Example 7
[0093] A method for preparing an artificial graphite negative electrode material is substantially the same as that in Example 2, except that:
[0094] In step (4), without a modifier, the spheroidized artificial graphite raw material is mixed and granulated with a mixture of petroleum asphalt and phenolic resin to obtain an artificial graphite precursor.
[0095] Experimental Example 1
[0096] The artificial graphitized negative electrode materials obtained in Examples 1 to 6 and Comparative Examples 1 to 7 of the same mass were weighed for performance testing, and the first discharge capacity, first discharge efficiency and powder compaction density of the negative electrode materials were tested with reference to the national standard GB / T 24533-2019 "Graphite Negative Electrode Materials for Lithium Ion Batteries", and the results shown in Table 1 were obtained.
[0097] Table 1 First discharge capacity, first discharge efficiency and powder compaction density
[0098]
[0099] It can be seen from Table 1 that, compared with Comparative Examples 1 to 7, the batteries containing the artificial graphite negative electrode materials of Examples 1 to 6 of the present invention have better first discharge efficiency; by comparing Examples 1, 3, 4 and 6, it is found that the artificial graphite negative electrode materials of Examples 4 to 6 have better powder compaction density, because sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate are used in the granulation step, and petroleum asphalt and phenolic resin work together to improve the compactness of the coating layer, and then the artificial graphite negative electrode material is obtained through carbonization and graphitization steps, so that the structure of the negative electrode material is more stable, the density of the graphite surface is improved, which is helpful to improve the energy density of the battery and make the deformation durability of the negative electrode material higher.
[0100] Compared with Examples 1 to 6, the first discharge efficiency of the battery of the artificial graphite negative electrode material obtained by increasing or decreasing the mass ratio of the coating material to the spheroidized artificial graphite raw material in Comparative Examples 1 to 2 is significantly reduced, indicating that in the production process, controlling the mass ratio of the coating material to the spheroidized artificial graphite raw material is helpful for the battery of the artificial graphite negative electrode material to achieve a better first discharge efficiency. The "protective cover" of the shell structure formed by coating the coating material on the surface of the spheroidized artificial graphite raw material can not only avoid the co-embedding and mixing of lithium ions and solvents and inhibit the decomposition of the electrolyte when used, but also improve the compatibility of the negative electrode material and the electrolyte. At the same time, the resin is coated on the surface of the negative electrode to make the formed coating layer tighter and firmer, which helps to shape the negative electrode material, so that the lithium battery has a larger capacity, a longer service life, and a faster charging speed.
[0101] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing an artificial graphite negative electrode material, It is characterized in that The method includes: (1) Crushing step: crushing the artificial graphite raw material once to obtain crushed artificial graphite raw material; (2) calcining step: calcining the crushed artificial graphite raw material at 160° C. to obtain a calcined artificial graphite raw material; (3) a crushing and shaping step: the calcined artificial graphite raw material is subjected to secondary crushing and then spheroidization to obtain a spheroidized artificial graphite raw material; (4) granulation step: mixing and granulating the spheroidized artificial graphite raw material and the coating material to obtain an artificial graphite precursor; Wherein, the coating material is a mixture of asphalt, resin and modifier; The modifier is a mixture of sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate; (5) Carbonization step: carbonizing the artificial graphite precursor at 700° C. to 1100° C. to obtain carbonized graphite particles; (6) Graphitization step: treating the carbonized graphite particles at a temperature of 2600° C. to 3200° C. to obtain a primary product of artificial graphite negative electrode material.
2. The preparation method according to claim 1, It is characterized in that The mass ratio of the coating material to the spheroidized artificial graphite raw material is 10:(30-80); the mass ratio of the asphalt, resin and modifier is 1:(2.5-3.5):(0.2-0.8).
3. The preparation method according to claim 2, It is characterized in that The mass ratio of the sodium dodecylbenzene sulfonate, tetrabutylammonium sulfate and melamine polyphosphate is 1:(0.5-0.8):(0.2-0.5); the artificial graphite raw material is a mixture of petroleum coke and needle coke in a mass ratio of 1:(5-8).
4. The preparation method according to claim 3, It is characterized in that Or the granulation step is: The modifier and water are mixed in a weight ratio of 1: (3-10) to obtain a modified dispersion; the spheroidized artificial graphite raw material and the modified dispersion are stirred at a temperature of 50-60° C. to obtain a modified artificial graphite primary product; the modified artificial graphite primary product is mixed and granulated with a mixture of asphalt and resin to obtain the artificial graphite precursor; The mass ratio of the spheroidized artificial graphite raw material to the modified dispersion is 10:(0.09-2), and the mass ratio of the artificial graphite modified primary product to the asphalt and the resin is (10-12):1:(2-4).
5. The preparation method according to claim 1, It is characterized in that The particle size of the crushed artificial graphite raw material is 3-10 μm, and the particle size of the spheroidized artificial graphite raw material is 5-20 μm; the volatile matter of the artificial graphite raw material after calcination is ≤1%; and the calcination time at 160° C. is 5-7 hours.
6. The preparation method according to claim 1, It is characterized in that The carbonization time is 2 to 5 hours, and the treatment time at 2600° C. to 3200° C. is 20 to 35 hours; the asphalt is petroleum asphalt or coal asphalt, and the resin is phenolic resin or epoxy resin.
7. The preparation method according to claim 1, It is characterized in that The method further comprises: screening and demagnetizing the primary product of the artificial graphite negative electrode material to obtain the artificial graphite negative electrode material.
8. An artificial graphite negative electrode material obtained by the preparation method according to any one of claims 1 to 7.
9. The artificial graphite negative electrode material according to claim 8, It is characterized in that The particle size of the artificial graphite negative electrode material is 10 to 22 μm.
10. Use of the artificial graphite negative electrode material according to claim 8 in the field of batteries.
Citation Information
Cited By
Asphalt solid-phase composition for coating, modified asphalt-coated natural graphite negative electrode material, preparation of modified asphalt-coated natural graphite negative electrode material and lithium ion battery
CN119320567A
Asphalt solid phase composition for coating, modified asphalt coated natural graphite negative electrode material and preparation thereof and lithium ion battery
CN119320567B
